Universal Service for Socially Excluded Users - B. Bakmaz; D. Bogojevic; N. Gospic; M. Petrovic (Telfor Journal, 2009)
This paper is about defining special measures within a universal service for potential socially excluded users, as a part of Project on US in Serbia. In the centre of research are people with disabilities, low income households, and welfare institutions in the Republic of Serbia. After analyzing regulations and statistical data, proposals for telecommunications services for these users are analyzed together with the costs of their realizations. At the end preliminary results of research are discussed.